Sosialisasi Bahaya Mengonsumsi Ikan Tercemar Di Desa Jirak Kecamatan Sajad - Widia Widia; Beryaldi Agam; Muhammad Zakiyul Fikri; Sangkala Sangkala; Oktavia Nurmawaty Sigiro; Nurul Fatimah Yunita; Asrul Asrul; Bayu Nugroho; Deya Agusriani; Jian Rifa Aldina; Joni Joni; Ludiyansyah Ludiyansyah; Masnita Masnita; Muhammad Faris Nurkholis; Marjulita Marjulita; Neny Neny; Ridho Ahyana (Pakis Journal Institute, 2024)
Water has a crucial role in human life and ecosystems, especially as a source of life. However, the sustainability of water sources, such as rivers, is threatened by industrial waste pollution, as happened to the Jirak River in Sambas City. This condition is caused by the poor system of Wastewater Sewerage (SPAL) and Wastewater Management Plant (WWTP), as well as the shortage of latrines around the river. In 2014, the Ministry of Environment of the Republic of Indonesia noted that 75% of rivers in Indonesia experienced heavy pollution, including the Jirak River. One of the main pollutants is mercury (Hg), which can be toxic and harmful to human health. Therefore, it is necessary to make prevention and counseling efforts to the community. The purpose of this counseling is to socialize about the dangers of consuming polluted fish in Jirak Village in the Jirak River area of Sambas Regency, and also provide awareness to the surrounding community to consume fresh fish that can be applied in people's lives in a sustainable manner. The location of this counseling is the Jirak River located in Sambas Regency, West Kalimantan Province. The approach used in this community service activity is to provide socialization and direct communication to mothers in Jirak Village. The socialization participants participated in the activity by actively discussing and experiencing increased knowledge and understanding of the dangers of consuming polluted fish.